Digital Holographic Printing Methods for 3D Visualization of Cultural Heritage Artifacts - Kang, Hoonjong; Stoykova, Elena; Berberova, Nataliya; Park, Jiyong; Kim, Youngmin; Sup Park, Joo; Hong, Sunghee; Ivanov, Branimir; Nazarova, Dimana; Malinowski, Nikola (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
Holography enables capture and reconstruction of the optical field scattered from three-dimensional (3D) objects. The hologram encodes both amplitude and phase of the field under coherent illumination, whereas photography records only the amplitude by incoherent light. 3D visualization feature of holography motivates expansion of research efforts dedicated to digital holographic imaging methods as a holographic display or a holographic printer. The paper presents two holographic 3D printing techniques which combine digital 3D representation of an object with analog holographic recording. Generation of digital contents is considered for a holographic stereogram printer and a recently proposed wavefront printer. These imaging methods could be applied to specific artifacts which are difficult to be recorded by conventional analog holography.